Chief Executive Officer (Ceo) Characteristics And Firm Value : Evidence From Malaysia - Amirah Amani, Ulul Azmi (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Nowadays, the capabilities and competency of top managers such as CEO are extremely crucial for each firms in order to emerge the business into the market. It is the determinants to a success or failure of a particular firm. The main purpose of this study is to examines the effects of CEO characteristics on firm value. The samples are annual reports from non-financial firms listed on the Bursa Malaysia during the period of 2013 to 2015. CEO characteristics of gender, age, education, ownership and network were developed based on the upper-echelon, agency and resource dependence theories. The result imply that these CEO network are negatively significant to Malaysia firms and play an important role in determining firm value. When CEO have a wider network they tend to lost focus because of having too much commitment which resulting to decrease the firm value. In addition, the firm characteristics consisting firm age, firm size and firm leverage also found significant to firm value. This study would contribute to assist academicians and practitioners about the various impact of CEO characteristics to firm value. For future research, this study emphasizes other measurements CEO characteristics that could effect firm value.